Effects of age and gender on young children's coping responses for a mildly stressful and uncontrollable event - Chu, Pei Yun (2015)
Despite the increasing interest and efforts to conceptualise children's coping, less is accomplished in the consolidation of developmental patterns. The present study seeks to undertake the task of identifying the developmental trajectories of coping responses for children ranging from two to seven years of age. YouTube videos of a hundred and forty-four children, in the event where Halloween candies were eaten up by their parents, were observed. The coping behaviours displayed by the children were coded using a newly devised coding scheme. The frequencies of behaviours were scored and analysed using MANOVA tests. The results revealed significant developmental differences in terms of self-distraction and other-blame for coping responses as well as accommodation and opposition families. Both self-distraction and accommodation behaviours seemed to decline with age while the other-blame and opposition behaviours appeared to increase with age.